Description of The Experiment: The Effectiveness of the Use of an Interactive Pedagogical Website by a Teacher of Russian as a Foreign Language - S. V. Marchuk (Открытое образование (Москва))
The purpose of the study. To describe a pedagogical experiment for the research work “Pedagogical conditions for the formation of communicative competencies in the digital educational environment of a Russian university (in the preparation of students from foreign countries)” on the example of the introduction of an interactive pedagogical website into the digital educational environment. The intended goal defined the tasks: 1) define the concept of pedagogical experiment; 2) state the essence of the subject of the experiment; 3) make a scientific description of the experiment. In pedagogical science, it is definitely not possible to conduct an experiment for a number of psychological and physiological reasons. To get a more accurate result, you need to use different methods. This research article presents two types of pedagogical experiment.Materials and methods. To define the concept of pedagogical experiment, we studied the works of A. Leontiev on active mind, O. Borovkova on the problem of experience in historical science, V. Zagvyazinsky and V. Slastenin on methodology, methods and the importance of didactic research. They turned to the philosophical encyclopedia and the vision of the modern philosopher E. Loone about the futility of conducting an experiment in the presence of a documentary source, although F. Bacon considers the pilot experiment to be extremely important and fundamental, and his thought served as an epigraph to the article. They turned to the psychological dictionary and noted that the experiment is defined as cognition. Having proved the effectiveness of teaching the introduction of information technologies in pedagogical conditions, we found out, analyzing the work of V. Krutetsky, what abilities a modern teacher should have. We stopped at the criteria of A. Sidenko’s pedagogical experiment. Using the methods of observation, description, analysis and survey, we described in the article a search and verification experiment using the method of concomitant changes. In addition, an experiment was conducted with two groups: experimental and control.Results. A pedagogical experiment cannot be as accurate as in fundamental science, so the value of the article lies in a detailed description of the pedagogical experiment. Different methods were used: concomitant changes, where the principle is causation, and a parallel method, where the effectiveness of the interactive pedagogical website was tested by comparing the results of the two groups. Conclusion. The author of the article proved that the pedagogical experiment must be carried out in different ways in order to bring its results closer to the most accurate ones. Our experiments, the results of which are reliable, have proved the effectiveness of using an interactive pedagogical website in preparing foreign students for studying at Russian universities.